Top down control of spinal sensorimotor circuits essential for survival. (24th April 2017) - Koutsikou, Stella; Apps, Richard; Lumb, Bridget M.
Abstract : Periaqueductal grey top down control of sensory and motor circuits. Schematic illustration of the dorsomedial (dm), dorsolateral (dl), lateral (l) and ventrolateral (vl) neuronal columns of the caudal periaqueductal grey (PAG) exerting their descending influences on spinal and supraspinal sensory and motor circuits. Effects of top down control on spinal neurones: red, inhibited; green, facilitated; and blue, no effect. Abstract: The ability to interact with challenging environments requires coordination of sensory and motor systems that underpin appropriate survival behaviours. All animals, including humans, use active and passive coping strategies to react to escapable or inescapable threats, respectively. Across species the neural pathways involved in survival behaviours are highly conserved and there is a consensus that knowledge of such pathways is a fundamental step towards understanding the neural circuits underpinning emotion in humans and treating anxiety or other prevalent emotional disorders. The midbrain periaqueductal grey (PAG) lies at the heart of the defence‐arousal system and its integrity is paramount to the expression of survival behaviours. To date, studies of 'top down control' components of defence behaviours have focused largely on the sensory and autonomic consequences of PAG activation. In this context, effects on motor activity have received comparatively little attention, despite overwhelming evidence of a pivotal role for the PAG in coordinating motor responses essential to survival (e.g. such as freezing in response to fear). In this article we provide an overview of top down control of sensory functions from the PAG, including selective control of different modalities of sensory, including proprioceptive, information forwarded to a major supsraspinal motor control centre, the cerebellum. Next, evidence from our own and other laboratories of PAG control of motor outflow is also discussed. Finally, the integration of sensorimotor functions by the PAG is considered, as part of coordinated defence behaviours that prepare an animal to be ready and able to react to danger.